Transformasi Organisasi untuk Meningkatkan Kreativitas Produk dan Inovasi Layanan - Ngadi Permana; Ruslaini Ruslaini; Muhammad Rizal (Jurnal Visi Manajemen, 2024)
This study aims to analyze the relationship between big bath accounting, corporate governance, and information asymmetry on audit fees through a qualitative literature review approach. Big bath accounting, a practice of manipulating earnings by reducing profits in one period to boost profits in the subsequent period, is known to increase audit risks, which subsequently leads to higher audit fees. Strong corporate governance is believed to mitigate the negative impact of this practice by providing more effective internal controls and reducing the level of information asymmetry. Low information asymmetry between management and shareholders reduces the auditor's uncertainty regarding the quality of financial statements, which can help lower audit fees. This study reviews recent literature on the relationship among these three variables, comparing findings from previous studies to provide a deeper and more comprehensive understanding. The study's findings suggest that good corporate governance and high levels of transparency play an important role in reducing audit fees caused by big bath accounting practices and information asymmetry. These findings are expected to contribute to the development of more effective governance policies that enhance financial transparency and control audit costs.